Pharmacological Properties of Sulfonamide Derivatives, New Inhibitors of Carbonic Anhydrase - Khokhlov, A. L.; Shetnev, A. A.; Korsakov, M. K.; Fedorov, V. N.; Tyushina, A. N.; Volkhin, N. N.; Vdovichenko, V. P. (Bulletin of experimental biology and medicine, 2023)
Selective blocking of individual isoforms of carbonic anhydrase (CA) is now one of the main directions in the development of its inhibitors. The new 1,2,4-oxadiazole-containing sulfonamides B12 and B13 predominantly block CA II and CA IX. The study of acute toxicity of B12 and B13 showed their safety. Substance B13 caused a relatively short-term, but rapid (within 30 min) decrease in the intraocular pressure in rabbits, which indicates the promise of its use for the emergency decrease in the intraocular pressure in medical practice. Analysis of the effects of sulfonamides on the functions of CNS showed that compound B12 probably exhibit tranquilizing activity; B13 is promising for the creation of drugs that have an antidepressant effect and at the same time increase the mental and physical performance.